Public Service Motivation and Interpersonal Citizenship Behavior in Public Organizations: Testing a Preliminary Model - Pandey, Sanjay K.; Wright, Bradley E.; Moynihan, Donald P. (My University, 2007)
This paper tests the relationships between individual levels of public service motivation and interpersonal citizenship behavior. The authors find that public service motivation increases organizational citizenship, even when accounting for the significant role of co-worker support.